1997
DOI: 10.1002/(sici)1097-0215(19970717)72:2<356::aid-ijc26>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β1 enhances the lethal effects of DNA‐damaging agents in a human lung‐cancer cell line

Abstract: In tissue culture conditions, exogeneous active transforming growth factor-b1 (TGF-b1) enhances the lethal effect of DNA-damaging agents (UV-C, gamma rays, cisplatin, methotrexate and 5-fluorouracil) toward human A549 cells and mink Mv1Lu cells, as detected by the loss of their capacity to give rise to colonies; both these cell lines harbor a wild-type p53, as determined by immunoprecipitation. Contrastingly, the sole effect of the cytokine used alone is to inhibit reversibly the multiplication of the same cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The number of PCNA‐positive cells increased in control cells compared with the cells before treatment with TGF‐β1 (A549 was 3.64% ± 3.63% and Panc‐1 was 9.28% ± 9.88%, respectively); however, we did not detect a significant difference between the control and TGF‐β1‐treated cells. The lower average percentage of PCNA‐positive cells among the TGF‐β1‐treated cells may indicate suppression of cell cycle progression in TGF‐β1‐treated cells, as reported earlier (Gibbs et al,2009; Raynal et al,1997). Based on these results, we concluded that TGF‐β1 did not affect the viability of A549 and Panc‐1 cells.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The number of PCNA‐positive cells increased in control cells compared with the cells before treatment with TGF‐β1 (A549 was 3.64% ± 3.63% and Panc‐1 was 9.28% ± 9.88%, respectively); however, we did not detect a significant difference between the control and TGF‐β1‐treated cells. The lower average percentage of PCNA‐positive cells among the TGF‐β1‐treated cells may indicate suppression of cell cycle progression in TGF‐β1‐treated cells, as reported earlier (Gibbs et al,2009; Raynal et al,1997). Based on these results, we concluded that TGF‐β1 did not affect the viability of A549 and Panc‐1 cells.…”
Section: Resultssupporting
confidence: 69%
“…The loss of filopodia may be mediated by abnormal formation/disassembly of actin filament structures because TGF‐β1 can cause actin filament production, but this awaits further study. However, growth suppression by TGF‐β1 may be a candidate mechanism as described in other studies (Gibbs et al,2009; Raynal et al,1997). In fact, in our preliminary experiment, mitotic arrest due to colcemide treatment also decreased the number of filopodia (data not shown).…”
Section: Discussionmentioning
confidence: 66%
“…Because TGF‐β1 can alter anti‐oxidant enzyme expression (Arsalane et al, 1997), it remains possible that the protective effects of TGF‐β1 were not due solely to growth arrest in G1. We were also concerned that further studies with TGF‐β1 may be problematic because it has been shown to directly affect cell viability as well as enhance the lethal effects of genotoxins (Sanchez et al, 1996; Raynal et al, 1997; data not shown). For these reasons, we examined whether serum deprivation, which also elicits a G1 arrest due to failure to activate G1 cyclin d ‐dependent kinase, altered survival during hyperoxia.…”
Section: Resultsmentioning
confidence: 99%
“…( 32 ) TGFβ1 is a 25‐kDa polypeptide that is involved in the regulation of many tissues, cells and organ functions, and enhances the lethal effect of DNA‐damaging agents including 5‐FU. ( 33 ) The TGFβ1/bone morphogenetic protein signaling pathway is not only required for cytokine signaling, but may also be an important factor for 5‐FU‐mediated apoptosis. ( 34 ) Midkine ( MDK ), located on chromosome 11p11.2, is a heparin‐binding growth factor that has been associated with the development of cancer, ( 35 ) and was consistently overexpressed in 5‐FU‐resistant cells compared with their parent cells.…”
Section: Discussionmentioning
confidence: 99%